The Roles of Javanese Phonology in Conveying Cultural Valuesin the Short Film Uba Rampe (2025) - Maulana, Adam; Anwar, Alifia Nabila Putri; Mabruroh, Siti; Lukman, Diva Sania (LPPM Universitas Bumigora Mataram, 2025)
This study aimed to examine how the phonological features of the Javanese language represent Javanese culture through the short film Uba Rampe (2025). This study used a qualitative descriptive method; the analysis focused on spoken utterances in the film that reflect elements of Javanese cultural representation. The research applied Chomsky’s theory of sound change to explain how specific phonological adaptations function as markers of cultural identity within the Javanese linguistic system. In addition, Poedjosoedarmo’s theory of linguistic politeness provides a framework for understanding how phonological variation can embody social values, particularly those related to respect and refinement in Javanese speech. The findings revealed several distinctive phonological phenomena, including phoneme alternations, allophonic variations, and aspiration patterns, which symbolize unique culturalcharacteristics of the Javanese language. Moreover, the presence of pre-nasalization in the utterances is a salient indicator of politeness, reflecting the Javanese emphasis on harmonious social interaction and deference. These phonological features were not merely linguistic markers but also served as representations of deeper cultural meanings embedded in everyday communication. Overall, this study demonstrated that the phonological system of Javanese plays a vital role in maintaining and expressing cultural identity, illustrating the intricate intertwining of language and culture within Javanese society.